Enhancing circular dichroism by super chiral hot spots from a chiral metasurface with apexes - Wang, Zeng (2017)
Manipulating light spin (or circular polarization) is an important research field and may find broad applications from sensors, display technology, to quantum computing and communication. To this end, planar metasurfaces with larger circular dichroism are strongly demanded. However, current planar chiral metasurface structures suffer from either fabrication challenge, especially from near-infrared to visible spectrum, or insufficient circular dichroism. Here, we report a chiral metasurface composed of achiral nanoholes which allow for precisely creating apexes in the designed structure. Our investigation indicates that the apexes act as super chiral hot spots and enable the highly concentrated near-field optical chirality leading to a remarkable enhancement of circular dichroism in the far-field. A 4-fold enhancement of the circular dichroism and a strong optical activity of ∼15 degrees have been experimentally achieved. Besides the enhanced chirality, our design genuinely overcomes the nanofabrication challenge faced in existing planar chiral metasurfaces.